RESPONS ORANG HIDUP DENGAN HIV AIDS (OHIDHA) DALAM UPAYA PENANGGULANGAN HIV AIDS DI KABUPATEN SUKOHARJO DAN GROBOGAN - Maqfiroch, Arrum Firda Ayu; Shaluhiyah, Zahroh; Margawati, ani (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2016)
Controlling HIV and AIDS requird involved People Living With HIV AIDS (PLWHA).  This study aims to determine the factors that determine whether the PLWHA response in control to HIV and AIDS in Sukoharjo Grobogan. This research was a quantitative study with cross sectional approach .This research was supported by qualitative research with FGD. The number of respondents was 92 PLWHA, the proportion of 50% and 95% confidence interval . Analysis of the data using univariate analysis with frequency distribution , bivariate using Chi-Square and multivariate using logistic regression . The results showed that the variables related to the PLWHA response is a relationship with people living with HIV ( p = 0,001 ) , long life with people living with HIV ( p = 0.030 ) , longer know the status of PLWHA ( 0.001 ) and attitude ( p = 0.005 ). Multivariate analysis showed that the attitude (p value = 0,006) was a variable that has the most significant effect compared to other variables .  Advice given to the government is to provide socialization on HIV AIDS comprehensively to the whole society by involving health agencies , NGOs , religious leaders and community leaders .